Roots to the Wings: The Apostolic Christ-Experience and Its Organic Growth in the Syro-Malabar Eucharistic Liturgy - Kaniarakath, George (Asian Horizons, 2020)
The book by Naiju Jose Kalambukattu CMI, Roots to the Wings: The Apostolic Christ-Experience and Its Organic Growth in the Syro-Malabar Eucharistic Liturgy is a well-researched scientific study, based on the sources. Originally a doctoral dissertation defended at Pontifical Oriental Institute, Rome, in 2017, it has now been brought out in a book form. Naiju Jose Kalambukattu, Roots to the Wings: The Apostolic Christ-Experience and Its Organic Growth in the Syro-Malabar Eucharistic Liturgy, Bengaluru: Dharmaram Publications, 2019, Pages: xxx+594. ISBN: 978-93-84964-10-8.